Glucose Transporter 1 Deficiency and Myoclonic Astatic Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2011)
Researchers at University of Melbourne, Australia; University of Florence, Italy; and University of Antwerp, Belgium performed genetic analysis on 84 unrelated probands with myoclonic-astatic epilepsy (MAE).